STUDI INTERAKSI MASYARAKAT MASA LAMPAU SUATU ANALISIS MODEL GRAVITI (GRAVITY MODEL) - Slamet Sujud Purnawan Jati (BRIN, 1999)
On this occasion, a model approach from Stephen Plog will be introduced. In this case, Plog tries to introduce a gravity model or gravity model to accurately predict the quantity of interactions between villages in a certain valley. Plog will prove that anthropologists, historians, and archaeologists can test the reliability of their own interaction measures using data from past societies. This model is carried out accurately and useful, and can be modified by new discoveries in the past.